THE UTILIZATION OF AMONIATED AND BIOFERMENTED RICE HULL IN DIETS AND SUPPLEMENTED PIPER BEETLE LEAF ON PERFORMANCE OF MALE BALI DUCK IN GROWTH PHASE - PARTAMA I. B. G.; T. G. B. YADNYA; A. A. A. S. TRISNADEWI (Fakultas Peternakan Universitas Udayana, 2018)
An experiment was carried out to study the effect on the use of amoniated and biofermented rice hull in diets andPiper beele leaf supplemented on performance of male bali ducks in growth phase. A completely randomized design(CRD) was used with five treatments, such as diet without rice hull (A), diets containing 10% rice hull (B), dietscontaining 10% amoniated and biofermented rice hull (C), diets containing 10% rice hull and Piper beetle leaf (D),diets containing 10% amoniated and biofermented rice hull and Piper beetle leaf (E). There were five female duckswith four replications in each treatment. The variables observed were diets consumption, degestible of diets, finalbody weight, body weight gain, and feed convertion ratio (FCR). It showed that 10% amoniated and biofermentedof rice hull fed to the ducks did not give effect to diets consumption (P>0,05). In contrast, feed digestibility, finalbody weight, body weight gain were significantly higher (P<0.05). Moreover, the FCR was lower compared to othertreatments. It can be concluded that amoniated and biofermented of rice hull, supplemented Piper beetle leaf canimprove performance of male bali duck in growth phase compared to other treatments.